AUDIT QUALITY: THE ROLE OF AUDIT TENURE, AUDITOR SWITCHING, AUDIT COMMITTEE AND TIME BUDGET PRESSURE - Hivianto, Laura Silvany; Kurniawati, Kurniawati (Jurnal Aplikasi Akuntansi, 2025)
The credibility of a company’s financial reporting depends largely on the quality of the audit process. This research explores how factors such as audit tenure, auditor switching, audit committee, and time budget pressure affect audit quality among property and real estate firms publicly traded on the Indonesia Stock Exchange (IDX) between 2019 and 2023. The research utilizes secondary data, comprising 250 observations selected through purposive sampling. The logistic regression model was conducted using EViews 10 as the primary statistical tool. These findings reveal that audit tenure positively influences audit quality, whereas auditor switching, audit committee, and time budget pressure do not have a significant effect. These results indicate that a longer auditor-client relationship enhances audit quality, as auditors gain a more comprehensive understanding of the client’s business and associated risks. These findings suggest that maintaining optimal audit tenure can support higher audit quality. It is recommended that management and regulatory authorities strike an appropriate balance between maintaining auditor familiarity and ensuring auditor independence and effective oversight.